2006
DOI: 10.1007/s11199-006-9110-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and Exercise Motivations: Are Gay Men and Heterosexual Women Most Likely to be Motivated by Concern About Weight and Appearance?

Abstract: This study was designed to investigate the relationship between sexuality and exercise motivations in 93 British bar staff. Participants who self-identified as heterosexual, gay, or lesbian completed the revised version of the Exercise Motivations Inventory and reported exercise frequency. Heterosexual men scored lower on appearance motives than did heterosexual women and gay men, higher on enjoyment motives than did gay men, and higher on competition motives than did women and gay men. Men were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Furthermore, a majority of participants described exercise and dieting as a tool to try to gain their perceived ideal figure, suggesting that there is a pressure among nonheterosexual women to conform to mainstream body ideals. These findings are in line with research by Grogan, Conner and Smithson (2006) who found that lesbian women engaged in similar levels of exercise and dieting as heterosexual women, in order to achieve a thinner, more toned, body. Furthermore, three participants discussed having experienced eating pathology at some point in their lives, suggesting that non-heterosexual women are also at risk for eating disorders, in line with previous research (e.g.…”
Section: Body-related Pressures and Influencessupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, a majority of participants described exercise and dieting as a tool to try to gain their perceived ideal figure, suggesting that there is a pressure among nonheterosexual women to conform to mainstream body ideals. These findings are in line with research by Grogan, Conner and Smithson (2006) who found that lesbian women engaged in similar levels of exercise and dieting as heterosexual women, in order to achieve a thinner, more toned, body. Furthermore, three participants discussed having experienced eating pathology at some point in their lives, suggesting that non-heterosexual women are also at risk for eating disorders, in line with previous research (e.g.…”
Section: Body-related Pressures and Influencessupporting
confidence: 91%
“…More recent research has suggested no significant differences in body dissatisfaction between heterosexual and non-heterosexual women (e.g. Grogan, Conner, & Smithson, 2006;Huxley, Clarke, & Halliwell, 2014;Peplau et al, 2009;Tiggemann, 2015), as well as similar levels of eating pathology (e.g. Austin et al, 2004;Feldman & Meyer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Adding to the complexity of clothing needs, age, sex, and physical activity, sexuality contributes to social pressure for physical attractiveness (Conner et al 2004). It has been found that heterosexual women and gay men experience more pressure to attain a slender figure than lesbians and heterosexual men (Grogan et al 2006).…”
Section: Researchmentioning
confidence: 99%
“…Adding to the complexity of clothing needs, age, sex, and physical activity, sexuality contributes to social pressure for physical attractiveness (Conner et al 2004). It has been found that heterosexual women and gay men experience more pressure to attain a slender figure than lesbians and heterosexual men (Grogan et al 2006).Due to the lack of published research on exercise clothing, this study analyzes what obese heterosexual women wear, their perceived choices, alternatives, and satisfaction in clothing for exercise. As an exploratory study, the authors did not want to limit discussion of exercise clothing to active wear specialty items.…”
mentioning
confidence: 99%
“…Dieting is more frequent among women than among men [15], who tend to practice physical exercise rather than diet to change the look of their bodies and to lose weight [16,17]. Moreover, improving body image, particularly by reducing its importance in one’s personal life, plays a role in enhancing eating self-regulation during weight control in women [18].…”
Section: Introductionmentioning
confidence: 99%